EEG-FCV: An EEG-Based Functional Connectivity Visualization Framework for Cognitive State Evaluation - Zeng, Hong; Jin, Yanping; Wu, Qi; Pan, Deng; Xu, Feifan; Zhao, Yue; Hu, Hua; Kong, Wanzeng (Frontiers in Psychiatry, 2022)
EEG-based tools for brain functional connectivity (FC) analysis and visualization play an important role in evaluating brain cognitive function. However, most of the existing methods are in 2-dimension (2D) and cannot visualize the FC intuitively. Besides, these methods cannot reflect the dynamic changes of brain FC and are prone to cause visual clutter. Therefore, we design and implement an EEG-based FC visualization framework in this study, named EEG-FCV, for brain cognitive state evaluation. Specially in EEG-FCV, FC is visualized in 3-dimension (3D) by introducing respectively three existing metrics: Pearson Correlation Coefficient (PCC), Coherence and PLV. Furthermore, a novel metric Comprehensive is proposed to eliminate visual clutter. We also provide dynamic visualization of EEG FC changes over time. And we conduct experiments on two available datasets and validate our framework through data visualization.Experimental results show EEG-FCV has consistent results with existing related studies on brain FC. In addition, EEG-FCV could also exhibits unique advantages in terms of dynamical changes of FC, which proves the effectiveness of EEG-FCV, and prompts the progress in brain cognitive function evaluation as well.